World watch geography skills Book 3 A geography skills book for grade 8 - Reilly, Carmel; Brasch, Nicholas (Karachi Oxford University Press, 2024)
Developed along the guidelines of national curriculum of Pakistan 2022. It is an extension of World watch social studies to the lower secondary level. It$1 (Bs aim to foster students$1 (Bgeographical literacy, spatial awareness, critical thinking and practical application of geographical concepts to enhance their overall understanding of the world and their place within it.s
Keywords: Geography